Biochemical characterization of two Brassica oleracea nitrile-specifier proteins - Mbudu, Kudzai Gracious; Witzel, Katja; Wittstock, Ute; Börnke, Frederik; Hanschen, Franziska Sabine (Frontiers in Plant Science, 2026)
Brassica oleracea vegetables (e. g. cabbages) form bioactive isothiocyanates (ITCs) from glucosinolate (GLS) hydrolysis. However, enzymatic activity, acidic pH (below pH 5), and ferrous ions (Fe2+) can promote nitrile release, reducing the ITC amount. In Arabidopsis thaliana, nitrile-specifier proteins (NSPs) promote nitrile formation upon GLS hydrolysis. Here, we report the functional characterization of two Brassica NSPs from B. oleracea and the in silico identification of candidate genes encoding a family of sixteen B. oleracea NSPs closely related to the A. thaliana NSPs and the likely ancestral protein, XP_013585314.1. High conservation of the iron-binding triad (EXXXDXXXH), characteristic of specifier proteins, was confirmed in the putative BoNSPs. Biochemical characterization of two B. oleracea NSP isoforms, BoNSP2 (XP_013609641.1) and BoNSP11 (XP_013587057.1), revealed increased NSP activity in the presence of added Fe2+. Both BoNSP isoforms affected hydrolysis of five GLS differently in vitro, suggesting differential substrate specificity. BoNSP2 showed higher nitrile formation from indol-3-ylmethyl GLS than from 4-(methylsulfinyl)butyl GLS. In contrast, BoNSP11 similarly increased nitrile formation from indol-3-ylmethyl GLS, three aliphatic GLS and benzyl GLS. BoNSP2 and BoNSP11 were most active between pH 7 and pH 8. This study identifies and characterizes the first NSPs in B. oleracea vegetables at the molecular level.